Firm Size, Liquidity, and Capital Structure as Determinants of Firm Value - Putri Delimah; Usdeldi; Puteri Anggi Lubis (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Firm value remains a central consideration for investors; however, empirical evidence regarding the effects of firm size, liquidity, and capital structure among Sharia-compliant automotive companies remains inconsistent. This study aims to examine the partial and simultaneous effects of firm size, liquidity, and capital structure on firm value. A quantitative approach with an associative explanatory design was employed using data from 12 automotive companies listed in the Indonesian Sharia Stock Index during 2020–2024. Purposive sampling yielded 60 firm-year observations. Secondary data were collected from financial statements and market information and analyzed using panel data regression with EViews 12. The findings indicate that firm size has a negative and significant effect on firm value, whereas liquidity has a positive and significant effect. Capital structure has a negative but statistically insignificant effect on firm value. Simultaneously, the three variables significantly affect firm value, although the model explains only 15.39% of its variation. These findings extend the application of signaling theory by showing that investors interpret corporate financial information based on asset utilization, short-term financial capacity, and financing risk. The study contributes empirical evidence on the determinants of firm value in the context of Sharia-compliant automotive companies. Practically, companies should improve asset productivity, maintain efficient liquidity levels, and align debt decisions with their cash-flow capacity. Future research should incorporate additional determinants, including profitability, dividend policy, corporate governance, and macroeconomic conditions. Keywords: Capital Structure; Firm Size; Firm Value; Liquidity; Sharia-Compliant Companies